Social Stratification And Conflicts Of Middle English Society In Geoffrey Chaucer’s The Canterbury Tales - Wati, Eni Lidia (Jurnal Ilmiah Mahasiswa FIB, 2015)
Societies in a country are usually included of some different social layers in common way they live. It shows how much difference and equality could distinguish them into grouping which have both positive and negative implications for the most. As seen, they generally have different life to each other, depending on their level in such way living together. Sometimes there would be a social injustice and conflicts to those who are segregated by strata of social classes. The crucial issue to which society divide the class, not surprisingly, often depends on how ironically they show their own power as the pride of life which could result social conflict in the end. It is common for social integration that is separated by very little physical appearance of social position and economical condition to be at opposite ends of the social gap. People who come from different strata, especially the upper class usually try to expose their abundance and glorious thing, like wealth, money, the pride of noble integrity, political power, and so many prestige things to underestimate the lower. On the other side, the under might feel envy watching the upper glory by that way, so it makes them do any unfair thing to get the upper down. What many people do not understand however is that it also threatens the social unity and its ideals ofgood living. This fragile thing is really dangerous to happen in any country all entire the world. It seriously can cause separation, amalgamation, social diversification, and even social conflicts which could destroy the peace of life. That is why every people should not differentiate social level for keeping a good harmony of socialization.In this case, the purpose of this study is to determine how the crucial problem ofsocial injustice in social stratification may result the social conflict for the life existence. It has already been analyzed and figured out into main point of this thesis research. Taken from the fiction characters which are reflected among the real people of Middle English society at the era, the writer has successfully analyzed and determined toward the defining social classes and the conflict problem itself in performing the Middle English social levels and how the conflicts happen portrayed in The Canterbury Tales by Geoffrey Chaucer book.The focus of this research study uses Social Class and Stratification theory ofPeter Saunders, as the main theory to use for finding a way to crack the problem analysis. The  writer uses the  theory above to  strengthen her thought about social  injustice in stratification. Peter Saunders has written the theory to develop a thought how social classes are divided and how inequality may arise and result the social conflict in society. It is the logical reason which the writer uses the theory as a foundation that is why.The results indicate a violation of social stratification could harm social harmonyin any such ways of life. What the social grouping and the conflicts itself that happen in The Canterbury Tales is just a depiction how much harmful a social classes existed into the social living. Many competitions, discriminations, public unfair, and so many other bad things that could be happen in this fragile way. It should not be happened anywhere we live, just to have a good way for happy life and to find the right one.  Keywords: Class, Social Class, Social Stratification, and Social Conflict.